EDUCATION TOWARDS HEALTHY AND INDEPENDENT OLDERING AT THE INDEPENDENT PLACE OF MIDWIFE PRACTICE L TANGERANG - Calada, Sri; Indrayani, Triana; Aquarini, Aquarini (Yayasan Education and Social Center, 2024)
The elderly are one of the groups or populations at risk (population at risk) whose numbers are increasing. Allender, Rector, and Warner (2014) said that the population at risk is a group of people who have health problems. The aim of community service intervention activities is to improve the health status of the elderly so that they remain healthy and independent. The method used in this intervention is counseling. The stages include pretest, counseling, question and answer, evaluation, door prize distribution. Participants were very enthusiastic and gave positive responses in the form of active participation in questions and answers in the discussion session. With this activity, elderly people will understand more about diseases that often occur in the elderly and how to prevent them and know how to maintain quality of life